2017
DOI: 10.1111/jpy.12565
|View full text |Cite
|
Sign up to set email alerts
|

The influence of species, density, and diversity of macroalgal aggregations on microphytobenthic settlement

Abstract: Intertidal macroalgae can modulate their biophysical environment by ameliorating physical conditions and creating habitats. Exploring how seaweed aggregations made up of different species at different densities modify the local environment may help explain how associated organisms respond to the attenuation of extreme physical conditions. Using Silvetia compressa, Chondracanthus canaliculatus, and Pyropia perforata, we constructed monocultures representing the leathery, corticated and foliose functional forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 80 publications
(144 reference statements)
0
7
0
Order By: Relevance
“…Before deployment at sea, 192 sporophytes were spliced into 48 braided polystrong ropes (6.35 mm in diameter, 36 cm in length) that were subsequently attached to plastic grids (36 × 30 cm) following the methods described in Umanzor et al. (). Each of the grids held four ropes and 16 sporophytes (i.e., four sporophytes per rope).…”
Section: Methodsmentioning
confidence: 99%
“…Before deployment at sea, 192 sporophytes were spliced into 48 braided polystrong ropes (6.35 mm in diameter, 36 cm in length) that were subsequently attached to plastic grids (36 × 30 cm) following the methods described in Umanzor et al. (). Each of the grids held four ropes and 16 sporophytes (i.e., four sporophytes per rope).…”
Section: Methodsmentioning
confidence: 99%
“…This effect, however, is not always consistent, as the strength of adhesion depends on the species of seaweeds tested, their stage of development and the physicochemical properties of the substrate (Mieszkin et al, 2013). Although this study was repeated a year later, similarly to Umanzor et al (2017), we found that diatoms of the genus Cocconeis almost solely colonized all understories. This result provides further evidence of the relevance of particle retention for the settlement of benthic organisms, as particle transport and deposition significantly influence their establishment, survival, and development (Eckman and Duggins, 1991;Morrow and Carpenter, 2008).…”
Section: Discussionmentioning
confidence: 66%
“…Abiotic factors can affect both the distribution and abundance of organisms, thus modulating community structure (Crain and Bertness, 2006). In a recent contribution, Umanzor et al (2017) explored how different seaweed aggregations influenced the abundance and distribution of understory microphytobenthic (MPB) organisms (benthic diatoms and cyanobacteria) on an exposed rocky intertidal. Results showed that the settlement of microphytobenthic organisms was modulated by the interaction between the species composition and the density of the seaweed aggregations, with branched morphologies at higher densities having higher particle retention and greater abundance of MPB organisms underneath their canopies.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely driven by differences in hydrodynamic stress attenuation and food availability rather than structural complexity per se (Bell et al, 2013). Canopies of macroalgae with greater structural complexity also promote spatial and temporal patchiness of microphytobenthos, with potential significant effects on the overall productivity of ecosystems (Umanzor et al, 2017). Fragmentation of seagrass canopies also alters their interactions with filter feeders.…”
Section: Distribution Of Canopy-dwelling Organismsmentioning
confidence: 99%